Sumber pertumbuhan sektor pertanian di Malaysia: satu analisis penyebab-akibat - Alias, Mohammad; Tuck, Cheong Tang (Sekolah Pengurusan, Universiti Utara Malaysia, 2003)
This paper examines the causal relationships between agricultural output and its sources of growth viz, primary commodity export,commercial bank lending and technology changes. Therefore, the applicability of export-led hypothesis for agriculture sector is tested. Johansen's cointegration approach and vector error correction model have been applied. The study uses the time series data for the period 1970-1998 (29 observations). The early result reveals the bias of using bivariate specification with no long run relationship between output and export for agriculture sector. However, the result of multivariate specification of Johansen's cointegration approach shows long run relationship between output, export, bank lending, and technology changes for agriculture sector with one cointegrating vector. The export's elasticity is 0.22. The coefficient of bank lending is insignzficant at 5 per cent level. The coefficient of trend variable is 0.024 that is interpreted as the output growth, which is related to technology changes. In the estimated vector error correction system, the significant of error- correction term in the error correction model for agricultural output growth confirms a unidirrectional causality that is from export growth and bank lending to agricultural output. No reversed causality. On the other hand, 44 per cent of disequilibrium in the short run can be successfully corrected by the agricultural output during a year period.